Alkali- and glutaraldehyde-modified pig blood as renewable adhesives for engineered bamboo products. Issue 8 (18th April 2021) - Guan, Mingjie; Chen, Xianwen; Zhang, Yuan; Tang, Xinyuan; Du, Keke; Yang, Sirui; Yong, Cheng
Abstract: Environmentally friendly fabrication of engineered bamboo lumber is enabled by the application of renewable, formaldehyde-free bio-adhesives. In this study, protein-based adhesives made from pig blood (PB) were developed for this purpose. PB was modified by alkali (NaOH) and glutaraldehyde into either alkali-modified pig blood adhesive (APB), glutaraldehyde-modified pig blood adhesive (GPB), or alkali-and-glutaraldehyde-modified pig blood adhesive (AGPB), which were expected to be more water-resistant. Two-ply laminated bamboo lumber samples were assembled, and their bonding strengths were measured. The thermal properties, presence of functional groups, and cross-sectional micro-morphologies of the modified adhesives and unmodified PB were characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The thermal stabilities of all the modified adhesives were improved compared to that of the unmodified PB. FTIR confirmed that the NaOH treatment successfully induced the unfolding of the PB protein, exposing the hydrophobic groups in the APB and that glutaraldehyde became grafted onto primary amides in the AGPB. Compared with the PB and APB, the cross-sectional micro-morphologies of the GPB and AGPB were more homogeneous and compact. The wet shear strength of the laminated bamboo lumber (LBL) was clearly increased by the modified adhesives. The AGPB had a higher wet shear strength of 4.6 MPa. Thus, the GPB and AGPB can be considered as potential protein adhesives for use in a variety of engineered bamboo products.